PROXIMATE ANALYSIS AND VITAMIN C CONTENT IN GREEN COCONUT (Cocos Nucifera L): ANALISIS PROKSIMAT DAN KANDUNGAN VITAMIN C PADA KELAPA HIJAU (Cocos Nucifera L) - Baihaqi; Fatahu; Ika Rezvani; Sri Agustina (PT. ROCE WISDOM ACEH, 2026)
This study analyzes the proximate composition, vitamin C content, and antioxidant activity of the water and flesh of young green coconuts (Cocos nucifera L.). Coconut water contains 7.19–8.20% carbohydrates, 29.35 mg/100g vitamin C, and 0.068–0.163% protein. The flesh contains 5.56–6.44% fat, higher protein levels, an average moisture content of 87.50%, and 0.88% ash. Antioxidant activity increases linearly in the water and fluctuates in the flesh. The results highlight coconut water's potential as an antioxidant source and the nutritional value of the flesh for food and health applications.